Inflation news coverage, expectations and risk premium - Daniel Perico Ortiz (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2023)
This paper investigates the effects of inflation news coverage on market-based inflation expectations and outcomes in the inflation-protected securities market. We employ a large corpus of news headlines from top U.S. newspapers and market data on the U.S. yield curve and inflation-protected securities. Our results indicate that news coverage, particularly regarding specific topics, exerts a significant influence on inflation compensation, expectations, and risk premiums. We observe that the impact of news diminishes as the maturity increases and varies across different news topics. This study contributes to the understanding of media influence on financial markets, specifically in shaping inflation expectations.
Keywords: C22; D83; D84; E13; E31; E65; 330; Inflation; expectations; risk premium; newspapers; term structure